2012
DOI: 10.1007/s10803-012-1629-2
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Responses to Odors in Children with High-Functioning Autism: Autonomic Arousal, Facial Behavior and Self-Report

Abstract: Although emotional functioning is impaired in children with autism, it is unclear if this impairment is due to difficulties with facial expression, autonomic responsiveness, or the verbal description of emotional states. To shed light on this issue, we examined responses to pleasant and unpleasant odors in eight children (8–14 years) with high-functioning autism and 8 age-matched typically developing controls. Despite subtle differences in the facial actions of the children with autism, children in both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 45 publications
2
36
1
7
Order By: Relevance
“…These results corroborate prior research that found more emotional response incoherence among children with ASD than TD children (e.g. Legiša et al 2013;McGee et al 1991). …”
Section: Expressive Incoherence In Asdsupporting
confidence: 91%
See 2 more Smart Citations
“…These results corroborate prior research that found more emotional response incoherence among children with ASD than TD children (e.g. Legiša et al 2013;McGee et al 1991). …”
Section: Expressive Incoherence In Asdsupporting
confidence: 91%
“…In a study assessing emotional responses to odors (Legiša et al 2013), children with ASD had similar expressive and physiological responses to the odors as TD children but the facial expressions of children with ASD were less likely to match their subjective experience. Moreover, children with ASD showed incoherence between subjective feelings of amusement and smiling and laughing behavior in a simple but effective humor task (Weiss et al 2013).…”
Section: Emotional Response Incoherence In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with ASD and TD children also exhibited similar facial expressions and autonomic responses to pleasant and unpleasant odors. Despite these similarities across diagnostic groups, children with ASD were less likely to report an emotional reaction to the odors that matched their facial response, indicating problems when self-reporting of emotional states (Legiša et al 2013). Moreover, several studies of children with ASD have drawn correlations between autonomic findings and psychosocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies has examined olfactory function in children and adolescents (Bennetto et al, 2007; Brewer et al, 2008; Dudova et al, 2011; Hrdlicka et al, 2011; May et al, 2011; Legisa et al, 2012); three studies have examined adults' responses (Suzuki et al, 2003; Tavassoli and Baron-Cohen, 2012b; Galle et al, 2013). All studies recruit high-functioning (HFA) participants.…”
mentioning
confidence: 99%